Kualitas Dan Daya Terima Sop Bakso Ikan Sebagai Makanan Anak Balita - Halipah, Siti; Faridah, Anni; Yuliana, Yuliana (Journal of Home Economics and Tourism, 2015)
This research aims to analysis the quality and to know capacity of acceptance sop bakso ikan. The kind of research which done is research development involving expert panelists who are the professional lecture in Tata Boga field, science of nutrition and food science. Object of the research is fish developed sop bakso ikan. Procedure in this research begins with determined standard recipe and the recipe was developed based on local potential. Sop bakso ikan which is developed then tested of validity until valid. Result of validity tested sop bakso ikan valid in the third trial. The recipe was sop bakso ikan developed it is fish 200 gr, tapioca flour 60 gr, salt 25 gr, garlic 18 gr, ice water 30 gr, sugar 2 gr, egg 5 gr, chives 37 gr, carrot 360 gr, potato 270 gr, red onion 15 gr, celery 5 gr, water 2000 ml,spices, oil 20 gr. The result of capacity acceptance test showed that sop bakso ikan which developed is received by toodlers seen from indicator edible portion, edible parts, expression of interest in food, end the length of time spent food, with on average avery indicator 75%. Key word: Quality, Capacity acceptance, Sop bakso ikan, Toodlers